Food‐web composition and plant diversity control foliar nutrient content and stoichiometry. (November 2015) - Borer, Elizabeth T.; Lind, Eric M.; Ogdahl, Eric J.; Seabloom, Eric W.; Tilman, David; Montgomery, Rebecca A.; Kinkel, Linda L.; Zanne, Amy
Summary The content and ratio of nutrients in plants can be constrained by a wide array of factors, including nutrient supply, light intensity, herbivory, infection or intrinsic growth rate and can, in turn, affect many ecosystem processes including photosynthesis, decomposition, resource limitation and nutrient cycling. Studies of plant stoichiometry and stoichiometric homeostasis have focused primarily on the role of nutrient supply as a constraint on plant tissue chemistry, yet recent work suggests that local plant diversity, plant species composition and consumers may change the nutrient composition of whole plant communities. By experimentally removing insects, foliar fungi and soil fungi from a long‐term experiment manipulating plant diversity, we found that the foliar stoichiometry of individual plant species depends on biotic context. Local plant diversity and the composition of the consumer community each altered foliar tissue carbon and nutrient chemistry of four different grassland species. The greatest impacts of consumers on foliar chemistry occurred at low plant diversity, and these changes induced by altering the food web were of a similar magnitude to the effects of fertilization or drought found in previous work. Consumers and plant diversity acted primarily on foliar carbon and nitrogen, whereas changes in foliar phosphorus were associated with the productivity of the local plant community. Thus, changes in whole‐community stoichiometry that have been documented in response to alterations of the consumer food web or plant community are underlain by stoichiometric changes in individual species as well as plant species compositional changes. Synthesis. These results suggest a new pathway by which loss of consumer or plant diversity may significantly impact the wide variety of ecosystem processes that depend on foliar nutrient content.